Analysis of Computer Information Security and Protection Strategies in the Era of Artificial Intelligence - Sun, Xiaofei; Zhou, Xiaoliang (Journal of Artificial Intelligence and Information, 2025)
Currently, there are still some problems and shortcomings in the operation of computer systems, such as illegal attacks, malicious destruction, and information leakage, which affect the stability of computer system development.In response to this, industry related technical personnel need to investigate and analyze current information security issues, realize the importance of information security protection, and develop scientific and specific solutions to the exposed problems to ensure the stability of computer system operation.This article explores how to maintain computer information security, aiming to promote the development of science and technology.